PENERAPAN TEXTILE MANIPULATION FABRIC TWISTING PADA KOLEKSI INSPIRASI KISAH RAMAYANA RAMA DAN SINTA CITYWEAR AUTUMN/WINTER 2023/2024 - Christabel Annora Paramita Parung; Dewa Ayu Sarastia Devi Suwasnita; Ninik Juniati (CALYPTRA, 2023)
Abstract–Fabric Manipulation is an technique of textile materials by utilizing fabrics to form fabric to create a new appearance. Fabric twisting is a textile manipulation which is made of two fabrics with different materials, color and textures. Twisting means to bend, to crook the fabrics into other shape. Fabric twisting can be done by a different way which will result in different looks. This study aims to identify how the Ramayana Rama and Sinta inspired-collection used the textile manipulation fabric twisting as its textile decoration. The study was to identify every step taken in the process of making fabric twisting from analyzing the visual of the story, creating shapes, and the decision to take fabric twisting as the textile manipulation. The result indicates that fabric twisting can symbolize one of the meanings from this story. The meaning is to symbolize the relationship between Rama and Sinta which are always connected even though they are separated by distance and time. Keyword: textile manioulation, fabric twisting, ramayana Abstrak – Fabric Manipulation ialah teknik merekayasa atau menghias bahan tekstil dengan memanfaatkan kain sehingga membentuk kain dengan tampilan baru. Fabric Twisting merupakan salah satu textile manipulation yang terbuat dari dua fabric dengan bahan, warna atau tekstur yang berbeda. Twist yang memiliki arti bengkok atau pelintir. Fabric twisting dapat dibuat dengan beberapa cara berbeda yang akan menghasilkan tampilan berbeda pula. Fabric twisting ini dapat diaplikasikan pada busana citywear yang terinspirasi dari kisah Ramayana Rama dan Sinta yang didapat dari trend forecast terbaru, care culture. Karena fabric twisting dapat melambangkan salah satu dari makna cerita kisah ini. Makna yang dimaksud ialah melambangkan hubungan yang erat antara Rama dan Sinta yang selalu terhubung walau terpisah jarak dan waktu. Keyword: textile manipulation, fabric twisting, ramayana